Укротительница мужчин, или Хищница: [роман] / Юлия Шилова - Шилова Юлия Витальевна (Русское криминальное чтиво, 2004)
Экземпляры: Ф. 10 (20200611) / Инвентарный номер: 47829 / Цена: 33.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Ш 59 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44